Examining the Gender Equality–Fertility Paradox in Three Nordic Countries - Katia Begall; Nicole Hiekel (Population and Development Review, 2025)
The accelerating fertility decline in the most gender-equal countries of the world seemingly contradicts the central tenet of macro-level theories that predict high fertility in the presence of gender equality. We offer a comprehensive assessment of the individual behavior from which these trends aggregate. We link attitudes toward gender roles and fertility intentions in three Nordic countries. Using recent data (2020–2022) and a multidimensional instrument on gender equality attitudes from the Generations and Gender Programme for Denmark, Finland, and Norway on n ~=~13,184 women and men, we identify three attitude profiles of which one is situated beyond the “non-egalitarian–egalitarian continuum.” The profiles are clearly associated with fertility intentions for childless individuals. We further provide evidence for two theoretical mechanisms that intervene between gender equality attitudes and fertility intentions. Gender-equal societies with a favorable opportunity structure for people to have the children they want may still face challenges associated with low fertility: Fertility intentions are lowest among egalitarians, that is, the largest population in these countries. While realizing a satisfying division of household labor with their partner enhances fertility intentions among egalitarians more than in the other groups, they do not necessarily prioritize parenthood as their main life objective.
Keywords: 300; gender role attitudes; fertility intentions; Nordic countries; fertility-equality reversal theories; second demographic transition; work-family reconciliation; parenthood as a life goal